A Systematic Review on Artificial Intelligence Applications for Enhancing EFL Students’ Pronunciation Skill - Aryanti, Risma Dwi; Santosa, Made Hery (STKIP AGAMA HINDU SINGARAJA, 2024)
This systematic literature review examines the impact of AI applications, including ELAi app, ELSA Speak, and Lyra Virtual Assistant, on the pronunciation skills of English as a Foreign Language (EFL) students. By analyzing ten relevant articles published between 2018 and 2023, this review identifies the unique features and effects of these AI tools. ELAi app emphasizes spontaneous speech and topic development, offering comprehensive feedback. ELSA Speak accurately detects pronunciation errors and provides a wide range of lessons. Lyra Virtual Assistant acts as a conversational companion, supporting speaking abilities. The findings reveal that these AI applications have a positive influence on EFL students' pronunciation development, as evidenced by empirical research. Further recommendations for future research in the integration of AI in EFL education is enhancing personalization through AI tools that adapt to individual students' learning styles and needs. In summary, utilizing AI technology can empower EFL students to improve their pronunciation proficiency and enhance their overall English language learning experience.